Comparison of Maximum Bite Force in Class Ш Skeletal Patients Before and After Orthognathic Surgery - Fatemeh Yari; Mehdi Rafiei; Arash Golestaneh; Eilnaz Ehrami (Isfahan University of Medical Sciences, 2022)
Orthognathic surgery not only changes the appearance of the face and the occlusion, but also changes the biomechanics and force of chewing. The aim of this study was to evaluate the maximum changes in byte force after orthognathic surgery in class III patients.Materials & Methods:In this clinical trial study, 20 class Ш skeletal patients referred to the School of Dentistry of Isfahan Azad University in the academic year 97-98 were selected and were divided into two groups before orthognathic surgery and 3 months after orthognathic surgery. The surgical technique in these patients was 2-jaw technique (Lefort 1 and BSSO). The area of the first right maxillary molar and the left maxillary first molar were measured at two intervals before surgery and three months after surgery. The sensor was first placed on one side of the first maxillary molar, then on the other side, and vice versa. The measurements were repeated three times on each side and the highest number was recorded as the patient's MBF (Maximum bite force). Data were analyzed using ANOVA and Tukey statistical tests (α = 0.05).Results:Mean maximum dental bite force was significantly decreased 3 months after surgery (p value < 0.001); this did not lead to a significant difference between maximum bite force and gender (p value = 0.244).Conclusion:Maxillofacial surgery in class III skeletal patients reduces the byte force in 3 months after maxillofacial surgery.